Centenarians and supercentenarians: a black swan. Emerging social, medical and surgical problems - Vacante, Marco (BioMed Central, 2012)
The Black Swan Theory was described by Nassim Nicholas Taleb in his book “The Black Swan”. This theory refers to “high-impact, hard-to-predict, and rare events beyond the realm of normal expectations”. According to Taleb’s criteria, a Black Swan Event is a surprise, it has a major impact and after the fact, the event is rationalized by hindsight, as if it had been expected. For most of human history centenarians were a rare and unpredictable phenomenon. The improvements of the social-environmental conditions, of medical care, and the quality of life caused a general improvement of the health status of the population and a consequent reduction of the overall morbidity and mortality, resulting in an overall increase of life expectancy. The study of centenarians and supercentenarians had the objective to consider this black swan and to evaluate the health, welfare, social and economic consequences of this phenomenon.